Does the architectural layout of a NICU affect alarm pressure? A comparative clinical audit of a single-family room and an open bay area NICU using a retrospective study design. Issue 6 (30th June 2018) - Joshi, Rohan; Straaten, Henrica van; Mortel, Heidi van de; Long, Xi; Andriessen, Peter; Pul, Carola van
Abstract : Objectives: To determine differences in alarm pressure between two otherwise comparable neonatal intensive care units (NICUs) differing in architectural layout—one of a single-family room (SFR) design and the other of an open bay area (OBA) design. Design: Retrospective audit of more than 2000 patient days from each NICU cataloguing the differences in the number and duration of alarms for critical and alerting alarms, as well as the interaction of clinicians with the patient monitor. Setting: Two level 3 NICUs. Results: A total of more than 150 000 critical and 1.2 million alerting alarms were acquired from the two NICUs. The number of audible alarms and the associated noise pollution varied considerably with the OBA NICU generating 44% more alarms per infant per day even though the SFR NICU generated 2.5 as many critical desaturation alarms per infant per day. Conclusion: Differences in the architectural layout of NICUs and the consequent differences in delays, thresholds and distribution systems for alarms are associated with differences in alarm pressure.